Factors that Influence Accounting Students' Interest in Careers in Sharia Banking (Empirical Study at Indo Global Mandiri University) - Indriyani, Indriyani; Munandar, Aris (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
This study aims to examine the influence of religiosity, Islamic accounting knowledge, labor market considerations, financial rewards, work environment, and family or friends on the interests of students accounting study program of Indo Global Mandiri University for a career in Islamic banking. The data used are primary data. The data collection technique was carried out by surveying 50 respondents. The data were analyzed using multiple linear regression analyses. The results prove that the consideration of the labor market, financial rewards, and the work environment have a positive effect on student interest in a career in Islamic banking. Meanwhile, religiosity, knowledge of Islamic accounting, and the environment of family or friends do not have a positive effect on student interest in a career in Islamic banking.